2011
DOI: 10.1111/j.1365-2621.2011.02793.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of debranching and heat-moisture treatment on the properties of Thai rice flours

Abstract: High and low amylose Thai rice flours (KC and ML, respectively) were used in this work, to increase the resistant starch (RS) content in the flour. Pullulanase debranching followed by heat-moisture treatment (DHMT) altered the pasting properties, which increased the shear stability to the flours. The gelatinisation temperature determined by DSC was increased and the more retrogradation occurred in treated flour compared to the native flour. The SEM observation showed that the treatment did not change the morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…SBP and SAP samples exhibited PV of 1050.3 and 290.7 cP and FV of 1435.0 and 626.3 cP, after 20 and 15 min of steaming, respectively. Satmalee & Matsuki () also observed changes in pasting properties and increase in shear stability in rice flour because of heat moisture treatment. Reduction in viscosity after hydrothermal treatment may be due to breakdown of starch granules (Rasper, ).…”
Section: Resultsmentioning
confidence: 92%
“…SBP and SAP samples exhibited PV of 1050.3 and 290.7 cP and FV of 1435.0 and 626.3 cP, after 20 and 15 min of steaming, respectively. Satmalee & Matsuki () also observed changes in pasting properties and increase in shear stability in rice flour because of heat moisture treatment. Reduction in viscosity after hydrothermal treatment may be due to breakdown of starch granules (Rasper, ).…”
Section: Resultsmentioning
confidence: 92%
“…In other studies, HMT in combination with these treatments increased the resistant starch yield. Satmalee and Matsuki reported that a combination of debranching and HMT applied in low amylose Thai rice flour increased the starch resistance. The effect of HMT in increasing the resistant starch yield when combined with other treatments was also revealed in Mutungi et al .…”
Section: Modification Of Starchmentioning
confidence: 99%
“…Rice flour can be modified in several ways, such as chemical, physical, and enzymatic methods [ 6 7 ]. Physical modifications involve pre-gelatinization and heat-moisture treatment [ 8 9 ], and have gained a wider application [ 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%